Procaspase- 3 Status in Benign Prostatic Hyperplasia and Carcinoma (A Correlative Retrospective Study) - Qader, Alaa A.; Rasheed, Nabeel W. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Benign prostatic hyperplasia and prostatic adenocarcinoma are two of the most common pathologic mass lesions. Both are encountered mainly in elderly males. The caspases family is a group of at least 15 known proteases that serve as initiator & effector molecules of the apoptosis pathway. Caspase-3, in particular, is thought to play a pathogenetic role in both prostatic hyperplasia and carcinoma. Finasteride is a medication that has routinely been given to patients with hyperplasia and carcinoma; its prostate size-reducing effect is thought to be mediated through caspases.Patients and methods: fifty patients with prostatic mass lesions were included in this study (20 with hyperplasia & 30 with adenocarcinoma); all were on finasteride treatment. The carcinoma cases were graded according to Gleason scoring system. All cases were analyzed for procaspase-3 strength of staining.Results: benign hyperplasia & well-differentiated carcinomas show high expression of procaspase-3, in contrast loss of expression of this marker was noted in moderately & poorly differentiated carcinomas.Conclusion: there is a strong statistical correlation between caspase-3 expression and the degree of tumor differentiation. This may allow the utilization of this marker as a potential prognostic factor, especially in limited biopsy samples.